2022
DOI: 10.1002/art.42246
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment for Hip and Knee Osteoarthritis Using Polygenic Risk Scores

Abstract: Objective. Polygenic risk scores (PRS) allow risk stratification using common single-nucleotide polymorphisms (SNPs), and clinical applications are currently explored for several diseases. This study was undertaken to assess the risk of hip and knee osteoarthritis (OA) using PRS.Methods. We analyzed 12,732 individuals from a population-based cohort from the Rotterdam Study (n = 11,496), a clinical cohort (Cohort Hip and Cohort Knee [CHECK] study; n = 908), and a high-risk cohort of overweight women (Prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This is the first study to identify the presence of mQTLs in human fetal cartilage and limb tissues, and our report demonstrates that the functional genetic risk of OA can be laid down during human skeletogenesis. Strides are being made within the field, with the first recent reports of polygenic risk scores (PRS) for the disease ( 52 , 53 ), yet the clinical utility of such systems is still lacking ( 54 ). We would encourage the integration of epigenetic data at the loci, along with clinical and biochemical parameters to further advance these tools for the patient benefit.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to identify the presence of mQTLs in human fetal cartilage and limb tissues, and our report demonstrates that the functional genetic risk of OA can be laid down during human skeletogenesis. Strides are being made within the field, with the first recent reports of polygenic risk scores (PRS) for the disease ( 52 , 53 ), yet the clinical utility of such systems is still lacking ( 54 ). We would encourage the integration of epigenetic data at the loci, along with clinical and biochemical parameters to further advance these tools for the patient benefit.…”
Section: Discussionmentioning
confidence: 99%
“…That said, it is known that variations in hip shape exist between European and East Asian populations (17). Future work, harnessing the resources of these large population studies with genetic data, could explore the incorporation of polygenic risk scores to assess whether their inclusion can enhance the performance of disease prediction models (39). In addition, if more cohorts become available then superior trans-ancestry GWAS techniques become possible such as meta-regression of multi-ancestry genetic association (MR-MEGA) (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these data sets might be used much earlier as prognostic tools, to determine patient risk and to direct prevention. For example, two recent studies used the loci identified in GWAS studies to determine the 'Polygenic Risk Score' (PRS) for OA patients, with encouraging results ( [30,31], discussed in [32]). Steinbeck et al [33] provide another example of using multiomics approaches to stratify patients and potentially direct more personalized treatments in the future.…”
Section: Outlook and Conclusionmentioning
confidence: 99%